The impact of neighbourhood walkability on the effectiveness of a structured education programme to increase objectively measured walking. (9th January 2017) - Carter, P; Bodicoat, D H; Jones, A; Khunti, K; Davies, M J; Edwardson, C L; Henson, J; Yates, T; Coombes, E
Abstract: Background: Incorporating physical activity into daily activities is key for the effectiveness of lifestyle education interventions aimed at improving health outcomes; however, consideration of the environmental context in which individuals live is not always made. Walkability is a characteristic of the physical environment, and may be a potential facilitator to changing physical activity levels. Methods: Using data collected during the Walking Away from Diabetes randomized controlled trial, we examined the association between the walkability of the home neighbourhood and physical activity of participants. We also determined whether home neighbourhood walkability of participants was associated with the intervention effect of the education programme. Results: Data from 706 participants were available for analysis. Neighbourhood walkability was not significantly associated with any of the physical activity measures at baseline, or at 12, 24 or 36 months following the intervention ( P > 0.05 for all). There was no association between walkability and change in purposeful steps/day from baseline to 36 months in the usual care or intervention arm; 25.77 (−99.04, 150.58) and 42.97 (−327.63, 413.45), respectively. Conclusion: Neighbourhood walkability appeared to have no association with objectively measured physical activity in this population. Furthermore, the walkability of participant's neighbourhood did not influence the effectiveness of a lifestyle programme.